The impact of environmental and agricultural pollutants on the prevalence of allergic diseases in people from Qassim, KSA - Elshabrawy, Walaa Othman; Ismail, Hisham Abdel-Sadek; Hassanein, Khaled Mohamed (International Journal of Health Sciences, 2014)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: There are multiple environmental factors that influence a sensitized (IgE antibody positive) patientâ€™s predisposition to manifest allergic symptoms following allergen exposure. The majority of allergens are known to induce morbidity with chronic symptoms such as rhinitis, pruritis, dermatitis and urticaria. Aim: To study the impact of environmental and agricultural pollutants with different pollens on the immunological, hematological and biochemical markers andto determine the prevalence of sensitization to allergens among exposed individuals as well as to identify the eliciting allergens. Subjects and Methods: Ninety six highly exposed individuals to environmental and agricultural pollution in addition to 20 as controls were selected. A solid phase enzyme-linked immunosorbent assay and the EUROLINE test kit were used for the quantitative determination of total IgE concentration and semi-quantitative in vitro assay of human IgE antibodies to some of the inhalant, ingestant and contactant allergens in serum samples, respectively. Percentage and absolute eosinophil counts and biochemical parameters were analyzed. Results: Thirteen (13.5%) out of the 96 studied highly exposed subjects were manifesting allergic symptoms. Higher significant total serum IgE levels and absolute eosinophil counts in groups 1 and 3 of the highly exposed individuals compared to the control group were found (p1=0.00, p3=0.001 and p1=0.016, p3=0.028, respectively). Higher sensitization with inhalant Timothy grass, Aspergillus fumigatus, Der. Farinae and Olive; ingestant Egg yolk, Mango, Strawberry and Codfish and with contactantLatex/plastic and Crude oil was found in the studied groups compared with the controls. Conclusion: The present data suggest that the highly exposed subjects to pollution are at high risk of developing an allergy. For the screening of those with suspected allergen sensitization, the determination of specific IgE antibodies is a suitable marker of type I allergy. Key words: Environmental and agricultural pollens, Recombinant allergens, Specific IgE antibodies.